Implementasi Pendidikan Karakter Dalam Pembelajaran PKn di Sekolah Dasar - Dewi Setiyaningsih; Fitria Rosmi; Gunawan Santoso; Annisa Virginia (STKIP Andi Matappa Pangkep, 2020)
This study aims to describe the implementation of character education through Citizenship education at the Noble Islamic School for the 2020 academic year, including learning planning, learning, character education assessment. This research is a descriptive study using a qualitative approach. This research was conducted at the Noble Islamic School with the subjects used were grade IV students and 1 principal and 2 teachers as informants. The results of the study were data obtained through observation, interviews, and documentation. The analysis technique in this study uses a data analyst with steps (1) data reduction (2) display / data presentation (3) draw conclusions and then verify. The implementation of the implementation of character education through Civics subjects at Noble Islamic School is in accordance with the planning made by the classroom teacher who teaches. The planning process is carried out by the teacher to determine the character values that will be developed in students. In the process of implementing learning, the teacher links character education into preliminary activities, core activities, and closing activities, finally in the process of assessing the implementation of character education, the teacher uses three assessments, namely, cognitive, affective, and psychomotor assessments.